Modeling the Effects of Formulary Exclusions: How Many Patients Could Be Affected by a Specific Exclusion? - Anne M. Sydor; Emily Bergin; Jonathan Kay; Erik Stone; Robert Popovian (Journal of Health Economics and Outcomes Research)
**Background:** Medication formularies, initially designed to promote the use of cost-effective generic drugs, are now designed to maximize financial benefits for the pharmacy benefit management companies that negotiate purchase prices. In the second-largest pharmacy benefit management formulary that is publicly available, 55% of mandated substitutions are not for generic or biosimilar versions of the same active ingredient and/or formulation and may not be medically or financially beneficial to patients.